EASIX for prediction of survival in lower-risk myelodysplastic syndromes - Merz, Almuth; Germing, Ulrich; Kobbe, Guido; Kaivers, Jennifer; Jauch, Anna; Radujković, Aleksandar; Hummel, Manuela; Benner, Axel; Merz, Maximilian; Dreger, Peter; Luft, Thomas (Blood cancer journal, 2019)
Patients with myelodysplastic syndromes (MDS) are at risk of early death from cardiovascular complications due to the link between clonal hematopoiesis and endothelial dysfunction. EASIX (Endothelial Activation and Stress Index) has been established to predict endothelial complications after allogeneic transplantation. We investigated the impact of EASIX measured at first diagnosis on survival of patients with lower- and higher-risk MDS (no allogeneic transplantation) in two independent institutions: n = 192 (training cohort) and n = 333 (validation cohort). Serum markers of endothelial cell distress were measured and correlated to EASIX. While no effects of EASIX on survival were observed in higher-risk patients, EASIX was associated with shorter survival in patients with lower-risk MDS in both cohorts (univariate: Cohort I: hazard ratio (HR): 1.46; 95% confidence interval (CI) 1.24-1.71; p-value < 0.001/Cohort II: HR 1.31 [1.17-1.48]; p-value < 0.001). Multivariate Cox regression analysis and prediction error analyses confirmed that EASIX remained a significant predictor of survival after adjustment for age, sex, cytogenetic abnormalities and bone marrow blasts in lower-risk patients. The model of the training cohort could be validated. Serum levels of Angiopioetin-2 correlated significantly with EASIX. We introduce EASIX as an easily accessible and independent predictor for survival in patients with lower-risk MDS.